A Spontaneous Uterine Rupture in Placenta Accreta Spectrum: a case series - Isharyah Sunarno; Deviana Soraya Riu; Andi Adil; Rachmawati Muhiddin; Juanita Juanita (Indonesian Socety of Obstetrics and Gynecology, 2026)
Objectives: Diagnosing uterine rupture in placenta accreta spectrum (PAS) can be challenging, often confirmed only during surgery after the rupture has occurred. This poses significant risks of morbidity and mortality for both the mother and neonates. Therefore, it is crucial for obstetricians to understand the clinical signs of uterine rupture in PAS cases. We aim to present four cases of grade 3a PAS and their associated maternal and neonatal outcomes related to spontaneous uterine rupture. Case management: Four cases of spontaneous uterine rupture attributed to FIGO grading 3A PAS occurred at Wahidin Sudirohusodo Hospital, a tertiary healthcare center in Makassar, South Sulawesi, Indonesia. All patients were multigravida with prior cesarean sections, presented at preterm gestational ages, and had histologically confirmed PAS. They were referred from secondary healthcare facilities. In two cases, spontaneous uterine rupture was identified prior to surgery, with the patients presenting in hypovolemic shock and intrauterine fetal demise. In the other two cases, the rupture occurred during laparotomy before any uterine procedure, and the neonates were delivered alive. During the emergency laparotomy, uterine ruptures were identified at the sites of placental attachment. In one case, an additional rupture was observed on the posterior uterine wall. Management included emergency classical cesarean section followed by supracervical hysterectomy, postoperative ICU admission, and massive blood transfusion. All mothers were discharged in stable condition. Conclusion: Spontaneous uterine rupture in PAS cases is associated with increased maternal morbidity as well as neonatal mortality and morbidity. Keywords: caesarean section, placenta accreta spectrum, spontaneous uterine rupture, classical cesarean section, supracervical hysterectomy